2018
DOI: 10.3847/1538-4357/aade46
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Observation of the 2017 November Glitch in the Crab Pulsar

Abstract: We have observed a glitch in the Crab pulsar (PSR B0531+21) in the 0.5–10 keV X-ray band with the X-Ray Pulsar Navigation-I (XPNAV-1) satellite. This glitch occurred around 2017 November 8. Observations at radio frequency by the Jodrell Bank observatory and the Lovell telescope have confirmed it to be the largest ever observed. We report the results of X-ray observation of this glitch. The measured rotation frequency increase of the Crab is Δν 0 = (14.3 ± 2.0) × 10−6 Hz, corresponding to a fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…Theν 0 of Zhang et al (2018) is an factor of two smaller than the value in Table 1. I believe these differences arise from the fact that firstly, the ν values listed by the JBCPME (from which Table 1 is derived) are themselves average values, mostly monthly averages, and secondly the preglitch durations of the three works may differ significantly; this may particularly affect the frequency second derivative. It is therefore concluded that there is broad agreement between the preglitch parameters derived here with those of Shaw et al (2018) and Zhang et al (2018), at least for the purpose of this work.…”
Section: Parametersupporting
confidence: 66%
See 2 more Smart Citations
“…Theν 0 of Zhang et al (2018) is an factor of two smaller than the value in Table 1. I believe these differences arise from the fact that firstly, the ν values listed by the JBCPME (from which Table 1 is derived) are themselves average values, mostly monthly averages, and secondly the preglitch durations of the three works may differ significantly; this may particularly affect the frequency second derivative. It is therefore concluded that there is broad agreement between the preglitch parameters derived here with those of Shaw et al (2018) and Zhang et al (2018), at least for the purpose of this work.…”
Section: Parametersupporting
confidence: 66%
“…Undertaking a similar exercise for the preglitch parameters of Zhang et al (2018), their ν 0 differs from the value in Table 1 above by −0.490 µHz; theirν 0 differs from the above value by −0.005 × 10 −12 Hz/sec. Theν 0 of Zhang et al (2018) is an factor of two smaller than the value in Table 1. I believe these differences arise from the fact that firstly, the ν values listed by the JBCPME (from which Table 1 is derived) are themselves average values, mostly monthly averages, and secondly the preglitch durations of the three works may differ significantly; this may particularly affect the frequency second derivative.…”
Section: Parametermentioning
confidence: 62%
See 1 more Smart Citation
“…This however has to be extrapolated to the convectively stable radiative regions of the atmosphere where a number of complex processes such as gravity waves and convective overshooting (Freytag et al 1996;Kupka et al 2018) may drive the mixing. The value of K zz has also been approximated from 3D numerical simulations of hot Jupiters including passive tracer transport (Parmentier et al 2013;Zhang & Showman 2018b). These approaches to estimating K zz have their limitations and none has provided a quantitative picture that has reached a consensus in the community.…”
Section: Chemistry Schemesmentioning
confidence: 99%
“…This irradiation leads to a slight increase in the radius relative to non-irradiated models, but when implemented in 1D structure models cannot explain the radius inflation of many hot Jupiters (Arras & Bildsten 2006, Fortney et al 2007). Irradiation powers atmospheric circulation that acts to transport heat both from day-to-night (Perez-Becker & Showman 2013, Komacek & Showman 2016) and vertically (Youdin & Mitchell 2010, Tremblin et al 2017, Zhang & Showman 2018, Komacek et al 2019, Sainsbury-Martinez et al 2019, but this is not included in our modeling framework. We model deposited heating as an additional term in the extra energy dissipation rate extra , as was done in previous studies of gaseous planet evolution with MESA (Wu & Lithwick 2013, Komacek & Youdin 2017, Millholland 2019.…”
Section: Numerical Modelmentioning
confidence: 99%